2013
DOI: 10.1126/scisignal.2003741
|View full text |Cite
|
Sign up to set email alerts
|

A Network of Substrates of the E3 Ubiquitin Ligases MDM2 and HUWE1 Control Apoptosis Independently of p53

Abstract: In the intrinsic pathway of apoptosis, cell-damaging signals promote the release of cytochrome c from mitochondria, triggering activation of the Apaf-1 and caspase-9 apoptosome. The ubiquitin E3 ligase MDM2 decreases the stability of the proapoptotic factor p53. We show that it also coordinated apoptotic events in a p53-independent manner by ubiquitylating the apoptosome activator CAS and the ubiquitin E3 ligase HUWE1. HUWE1 ubiquitylates the antiapoptotic factor Mcl-1, and we found that HUWE1 also ubiquitylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 46 publications
0
57
0
Order By: Relevance
“…[23][24][25] We found that knockdown of TRAF6 by specific siRNA, but not Mdm2 or Smurf2 knockdown, resulted in decreased PDGF-BB-induced ubiquitination of SM22α ( Figure 4A and 4B). To further verify this finding, 293 cells were transfected with HA-SM22α along with Flag-TRAF6 or the Flag-TRAF6 C70A mutant, which has lost E3 ligase activity.…”
Section: Traf6 Mediates K63-linked Ubiquitination Of Sm22αmentioning
confidence: 94%
“…[23][24][25] We found that knockdown of TRAF6 by specific siRNA, but not Mdm2 or Smurf2 knockdown, resulted in decreased PDGF-BB-induced ubiquitination of SM22α ( Figure 4A and 4B). To further verify this finding, 293 cells were transfected with HA-SM22α along with Flag-TRAF6 or the Flag-TRAF6 C70A mutant, which has lost E3 ligase activity.…”
Section: Traf6 Mediates K63-linked Ubiquitination Of Sm22αmentioning
confidence: 94%
“…44 Increased binding of RPL11 to MDM2 consecutive to ribosome biogenesis dysfunction could therefore potentially interfere with other p53-independent functions of MDM2 such as inhibition of apoptosis. [46][47][48] So far, such functions has been described in cell lines and it will be interesting in future studies to evaluate their contribution to the phenotype of NleVilcKO; p53KO mice.…”
Section: Discussionmentioning
confidence: 99%
“…HUWE1 is an E3 ubiquitin ligase that ubiquitinates multiple signaling proteins (44)(45)(46). Therefore, we examined whether HUWE1 catalyzes the ubiquitination of Shoc2 or its signaling partner, RAF-1.…”
Section: Resultsmentioning
confidence: 99%